2014
DOI: 10.1074/jbc.m114.603282
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of the Plant Small GTPase OsRac1 Reveals Its Mode of Binding to NADPH Oxidase

Abstract: Background:The plant small GTPase OsRac1 plays an important role in rice innate immunity. Results: The crystal structure and NADPH oxidase-binding mode of active-form OsRac1 were determined. Conclusion: The structure explains the mechanism by which OsRac1 regulates reactive oxygen species production and activates the immune response. Significance: A new insight into the activation of plant immunity by small GTPase is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…OsRbohB acts downstream of Os-Rac1 through a direct interaction of its N-terminal EF-hand motif with GTP-bound Os-Rac1 (Wong et al, 2007;Oda et al, 2010;Kosami et al, 2014), and, as shown in this study, Os-RbohH is also involved in Rac1-mediated immunity. Proteome analyses have identified Rbohs in DRMs of tobacco, Arabidopsis and rice (Morel et al, 2006;Kierszniowska et al, 2009;Fujiwara et al, 2009), and ROS production by Rbohs in pollen tube tips is dependent on PM microdomains in Picea meyeri (Liu et al, 2009).…”
Section: Role Of Pm Microdomains In the Rac1-rbohb/h-mediated Mti Patmentioning
confidence: 81%
See 1 more Smart Citation
“…OsRbohB acts downstream of Os-Rac1 through a direct interaction of its N-terminal EF-hand motif with GTP-bound Os-Rac1 (Wong et al, 2007;Oda et al, 2010;Kosami et al, 2014), and, as shown in this study, Os-RbohH is also involved in Rac1-mediated immunity. Proteome analyses have identified Rbohs in DRMs of tobacco, Arabidopsis and rice (Morel et al, 2006;Kierszniowska et al, 2009;Fujiwara et al, 2009), and ROS production by Rbohs in pollen tube tips is dependent on PM microdomains in Picea meyeri (Liu et al, 2009).…”
Section: Role Of Pm Microdomains In the Rac1-rbohb/h-mediated Mti Patmentioning
confidence: 81%
“…Os-Rac1 interacts with the N-terminal EF-hand motif of Os-RbohB, leading to an increase in ROS production (Wong et al, 2007;Oda et al, 2010;Kosami et al, 2014). To understand whether PM microdomains are necessary for ROS production mediated by the Rac1-Rboh pathway, we measured ROS production in OsFAH1/2-KD using the L-012 reagent.…”
Section: Os-fahs Are Involved In Ros Production After Chitin Treatmentmentioning
confidence: 99%
“…Within the G domain, ROPs also contain a helical domain unique to the Rho family known as the insert region or ai. The structural conservation of the G-domain has been confirmed by three-dimensional crystal structures of the GDP-bound Arabidopsis ROP9 (Sørmo et al, 2006), ROP4 in complex with the catalytic PRONE (for Plant-Specific ROP Nucleotide Exchanger) domain of ROPGEF3 , ROP5 (Thomas and Berken, 2010; Protein Data Bank code 3BWD), the nucleotide-free ROP7 in complex with the PRONE domain of ROPGEF8 (Thomas et al, 2009), and GTP-bound rice RAC1 (Kosami et al, 2014;Fig. 2, B-D).…”
Section: Structure/functionmentioning
confidence: 85%
“…Conversely, mutations in a G1 Thr (T20 in Arabidopsis ROP1-ROP6, ROP7, and ROP9; T22 in ROP10 and ROP11; and T32 in ROP8) or a G4 Asp (D121 in Arabidopsis ROP1-ROP6, ROP7, and ROP9; D123 in ROP10 and ROP11; and D133 in ROP8) are dominant negative (DN), reducing affinity for nucleotides and stabilizing the interaction with GEFs, thereby preventing ROP activation (Berken and Wittinghofer, 2008). In addition to the structural conservation of ROPs, the functional conservation of the constitutively active and dominant-negative mutations was confirmed by biochemical assays (Berken et al, 2005;Sorek et al, 2010;Kosami et al, 2014). The constitutively active and dominant-negative ROP mutants have been used extensively to study ROP function.…”
Section: Structure/functionmentioning
confidence: 96%
See 1 more Smart Citation